FIGURATIVE LANGUAGE ON TOURISM MAGAZINE: AN EQUIVALENT TRANSLATION - Raisya Syahma Aqila; Tarisa Fingky; Ni Nyoman Tri Sukarsih (Seminar Ilmiah Nasional Teknologi, Sains, dan Sosial Humaniora (SINTESA), 2023)
This study aims to analyze the English figurative language and its equivalent translation intoIndonesian found in the tourism magazine. The qualitative descriptive method is used in thisstudy to analyze the data. The source of the data was a tourism magazine, Api Bali, EnglishIndonesian version. Data were collected from Api Bali Magazine, Vol. 30. The theory offigurative language types by Tarigan (2009) and lexical equivalent translation, which is usedto obtain word equivalence in figurative language by Larson (1998), is used in this study. Theresult showed that there were five types of figurative language found in the tourism magazine:metaphor, simile, hyperbole, personification, and euphemism. The equivalent translation offigurative language uses related words as equivalents for metaphor and personification,descriptive phrases for hyperbole, and simile and euphemism use literally translation fromsource language to target language